Application of Aerosol Nanocatalysis Technology in Methane Steam Reforming - Glikin, Marat Aronovich; Kudryavtsev, Sergiy Alexandrovich; Mahmmod, Saif Mohammed A. (Journal of Petroleum Research and Studies, 2017)
Steam Methane Reforming (SMR) is the main method to obtain synthesis gas in production of alcohol, ammonia, acids Fischer-Tropsch synthesis and other organic products. The study has investigated the reaction of SMR and it mechanism, explained the aerosol nanocatalysis (AnC) vibrated bed as alternative technology instead of using heterogeneous catalyst in bed. The research has proven that NiO is the best catalyst that could be used in the reaction of SMR by AnC after investigating catalysts: Fe2O3, K-905D2, GIAP-8, Co2O3 and NiO.